Into the Andes: multiple independent colonizations drive montane diversity in the Neotropical clearwing butterflies Godyridina. Issue 22 (8th October 2016) - Chazot, Nicolas; Willmott, Keith R.; Condamine, Fabien L.; De‐Silva, Donna Lisa; Freitas, André V. L.; Lamas, Gerardo; Morlon, Hélène; Giraldo, Carlos E.; Jiggins, Chris D.; Joron, Mathieu; Mallet, James; Uribe, Sandra; et al.
Abstract: Understanding why species richness peaks along the Andes is a fundamental question in the study of Neotropical biodiversity. Several biogeographic and diversification scenarios have been proposed in the literature, but there is confusion about the processes underlying each scenario, and assessing their relative contribution is not straightforward. Here, we propose to refine these scenarios into a framework which evaluates four evolutionary mechanisms: higher speciation rate in the Andes, lower extinction rates in the Andes, older colonization times and higher colonization rates of the Andes from adjacent areas. We apply this framework to a species‐rich subtribe of Neotropical butterflies whose diversity peaks in the Andes, the Godyridina (Nymphalidae: Ithomiini). We generated a time‐calibrated phylogeny of the Godyridina and fitted time‐dependent diversification models. Using trait‐dependent diversification models and ancestral state reconstruction methods we then compared different biogeographic scenarios. We found strong evidence that the rates of colonization into the Andes were higher than the other way round. Those colonizations and the subsequent local diversification at equal rates in the Andes and in non‐Andean regions mechanically increased the species richness of Andean regions compared to that of non‐Andean regions ('species‐attractor' hypothesis). We also found support for increasing speciation rates associated with Andean lineages. Our work highlights the importance of the Andean slopes in repeatedly attracting non‐Andean lineages, most likely as a result of the diversity of habitats and/or host plants. Applying this analytical framework to other clades will bring important insights into the evolutionary mechanisms underlying the most species‐rich biodiversity hotspot on the planet.